Elevated serum neuregulin 4 levels in patients with hyperthyroidism. Issue 6 (June 2019) - Li, Min; Chen, Ying; Jiang, Jingjing; Lu, Yan; Song, Zhiyi; Zhang, Shengjie; Sun, Chao; Ying, Hao; Fan, Xiaofang; Song, Yuping; Yang, Jialin; Zhao, Lin
Abstract : Objective: Recent studies have shown that neuregulin 4 (Nrg4), a member of the epidermal growth factor (EGF) family of extracellular ligands, plays an important role in the prevention of obesity, insulin resistance and nonalcoholic fatty liver disease (NAFLD). Considering that thyroid hormone (TH) has profound effects on whole-body energy metabolism, we speculate that circulating Nrg4 levels might be altered in patients with hyperthyroidism. Design and methods: A total of 129 hyperthyroid patients and 100 healthy subjects were recruited. Of them, 39 hyperthyroid patients received thionamide treatment for 3 months until euthyroidism. Serum Nrg4 levels were determined using the ELISA method. To further confirm the relationship between TH and Nrg4, C57BL/6 mice were treated with T3 and quantitative real-time PCR was performed to detect Nrg4 gene expression. Results: Serum Nrg4 levels were significantly elevated in hyperthyroid patients as compared with normal controls (3.84 ± 1.63 vs 2.21 ± 1.04 ng/mL, P  < 0.001). After achieving euthyroidism by thionamide treatment, serum Nrg4 levels dropped markedly from 3.57 ± 1.26 to 1.94 ± 0.72 ng/ml ( P  < 0.001). After adjustment for potential confounders, serum Nrg4 levels were independently associated with hyperthyroidism. The upregulation of Nrg4 expression in the livers and white adipose tissues by T3 was further confirmed by animal and cell culture experiments. Conclusions: Serum Nrg4 levels were increased in patients with hyperthyroidism. The liver and white adipose tissue might be primary sources contributing to elevated serum Nrg4 concentrations.